RELATIONSHIP OF THE STATE OF BIOMEMBRANES WITH INDICATORS OF ENDOTHELIUM DYSFUNCTION IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE - A. M. SABUROVA; KH.R. NASYRDZHANOVA; KH.YO. SHARIPOVA (Avicenna Tajik State Medical University, 2020)
Objective: Examination the relationship between the state of biomembranes and indicators of endothelial dysfunction in patients with chronic obstructive pulmonary disease (COPD). Methods: 40 patients with COPD at the age of 27-64 years were treated at the City Health Center № 2 named after academician K.T. Tadzhiev. There were 21 men (52.5%), and 19 women (47.5%). The control group is represented by 30 healthy persons, comparable by sex and age. The content of inflammatory markers of vascular endothelium - CRP, fibrinogen and von Willebrand factor (VWF) - was studied. The functional state of erythrocyte membranes was studied by determining of permeability of erythrocyte membranes (PEM) and sorption ability of erythrocytes (SAE). Results: Study of endothelial dysfunction in patients with COPD showed an increase in fibrinogen content by 71.15% (2.6±0.08 and 4.45±0.16 g/L), VWF by 35.4% (95.7±2.3 and 129.6±2.3%) and an increase in serum CRP by 15 times (2.09±0.1 and 32.2±0.1 mg/L). There was a change in PEM and an increase in SAE by 27.8% (39.5±0.5 and 50.5±0.6%, respectively) compared with the control group, that reflects damage of erythrocytes and is considered as a factor of endogenous intoxication. A significant direct relationship was established between SAE and indicators of vascular dysfunction: with VWF (r=0.34; p<0.05) and fibrinogen (r=0.47; p<0.05). Conclusion: The development and progression of COPD are accompanied by dysfunction of the vascular endothelium, the criteria for which are an increase in the level of CRP, fibrinogen and VWF. On the background of COPD, erythrocytes are involved in the pathological process, which is confirmed by an increase in PEM and SAE and with a significant relationship between SAE and endothelial dysfunction. Laboratory manifestations of endothelial dysfunction accompanied by functional impairment of biomembranes (increased PEM and increased SAE), can be considered as a factor of the poor prognosis of COPD.